Solving simple problems of thermal power plants using simulation techniques - Ilirjan Malollari; Lorina Ligi (Zaštita Materijala)
A steam/thermal power station uses heat energy generated from burning coal to produce electrical energy. Because of the huge amounts of fuel (coal), this kind of power station can be used to produce large amounts of electrical energy. Wide range of commercial heat and mass balance simulation, analysis and optimization software packages are available on the market. In this paper is presented the use of IPSEpro from SimTech Simulation Technology. The so called software IPSEpro is an exploiting engineering system for calculating heat and mass balances and simulating processes, as well. In the study are presented some simple problems of thermal power plants to calculate mass and energy balances using the simulation program. With this program it was for us possible to analyze the performance of a standard plant as well as the investigation of the influence of particular components on the whole system. Therefore, the constructive design of particular power plant components can be implemented or improved based on the results of the simulations being performed. Our paper is presenting some real simple problem solution using the above mentioned simulation procedure, and we have calculated process conditions through mass and energy balances. Also we have shown the graphical presentation of the most important parameters governing the process for different units of the entire plant.